Sustainable food processing - Norton, Tomas; Tiwari, Brijesh K.; Holden, Nick. (Chichester, West Sussex, UK : Wiley Blackwell, 2013)
With global inequalities becoming more pronounced, ingredient costs climbing, and global warming a major political issue, food producers must now address environmental concerns, social responsibility and economic viability when designing their food processing techniques for the future. Sustainable food processing is all about finding new ways of meeting present needs without comprising future viability, given constantly changing economic and environmental conditions. This is not just a corporate social responsibility issue, but relates directly to efficiency, cost-saving and profitability.
5.1 Introduction5.2 Defining the objectives; 5.3 Wastes from food processing; 5.4 EIA methodology; 5.5 Environmental indicators; 5.6 Functional units; 5.7 Evaluation of results; 5.8 Conclusions; References; 6 Risk Analysis for a Sustainable Food Chain; 6.1 Introduction; 6.2 Approaches to risk analysis for a sustainable food chain; 6.3 Risk assessment (RA) strategies in the food chain; 6.3.1 Quantitative and qualitative RA in the food chain; 6.3.2 Stages of risk assessment; 6.4 Risk management (RM); 6.5 Risk communication (RC) strategies; 6.6 Role of risk analysis from farm to fork.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Food industry and trade; Processed foods; Food industry and trade -- Environmental aspects; Sustainable agriculture; TECHNOLOGY & ENGINEERING / Food Science; Food industry and trade; Food industry and trade -- Environmental aspects; Processed foods; Sustainable agriculture; Food industry and trade -- Environmental aspects; Food industry and trade; Processed foods; Sustainable agriculture; Electronic books; Electronic books